In vivo therapeutic potential of combination thiol depletion and alkylating chemotherapy. - Siemann, D. W. (Nature Publishing Group, 1993)
The effect of administering the thiol modulating agent buthionine sulfoximine (BSO) in conjunction with alkylating chemotherapy was investigated in vivo in the mouse KHT sarcomas and bone marrow stem cells. Tumour response to treatment was assessed by an in vivo to in vitro excision assay and bone marrow survival was determined in vitro by CFU-GM. Glutathione (GSH) depletion and recovery kinetics were determined at various times after treatment using high performance liquid chromatography (HPLC) techniques. Following a single 2.5 mmol kg-1 dose of BSO, tumour GSH reached a nadir of approximately 40% of control 12-16 h after treatment. Bone marrow GSH was depleted to approximately 45% of control 4-8 h after treatment but recovered to normal by 16 h. When a range of doses of CCNU, mitomycin C, cyclophosphamide or melphalan (MEL) were given 16 h after mice were exposed to a 2.5 mmol kg-1 dose of BSO, only the antitumour efficacy of MEL was effectively enhanced (by a factor of approximately 1.4). This BSO-MEL combination appeared to be selective for the tumour as the bone marrow toxicity was not increased beyond that seen for MEL alone. Since increasing the administered dose of BSO neither increased the extent of thiol depletion in the tumour nor enhanced the antitumour efficacy of MEL, three other protocols for delivering the thiol depletor were explored. BSO was given either as multiple 2.5 mmol kg-1 doses administered at 6 or 16 h intervals or continuously at a concentration of 30 mM supplied in the animals' drinking water. Both multi-dose BSO pretreatments were found to increase both the antitumour efficacy and normal tissue toxicity of MEL such that no advantage compared to the single dose combination was achieved. In contrast, maintaining the thiol depletor in the drinking water led to an approximately 1.7-fold increase in the antitumour efficacy of MEL without any corresponding increase in bone marrow stem cell toxicity. For the various pretreatment strategies it was possible, in all cases, to account for the presence or absence of a net therapeutic benefit on the basis of the tumour and bone marrow GSH depletion and recovery kinetics.